Undergraduate Students’ Morphological Awareness and Difficulties in EFL Class - Yulianawati, Ida; Yoga Prawiro, Indra; Anggrarini, Natalia (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
Students' vocabulary knowledge is related to their morphological awareness, which plays an essential role in word comprehension and vocabulary development. This case study is aimed at describing undergraduate students’ morphological awareness and difficulties in morpheme identification and word relationship. This study employed the MAT test in two analytical tests. The Morpheme Identification Test is used to measure how well first-year college students can analyze and break down complicated words into their smaller meanings. Meanwhile, the Word Relation Test is administered to measure undergraduate students’ awareness of relations among base or root words and their inflected or derived forms. An interview was used to support the results of the tests. The result showed that the students performed better in breaking down inflected forms than those in derived forms. As in the Word Relation Test, it was discovered that the students had done better in identifying morphologically related word pairs. There were three types of difficulties in the morpheme identification test. The first was in breaking down complex words into smaller morphemes; the second was in stating the meaning of each smaller morpheme, especially affixes; and the third was in categorizing the complex words into inflected or derived forms.